An Exploratory Study of Online Consumer Engagement on Social Media and its impact on Purchase Intention - Teh, Sook-Ching (2013)
The emergence of the social media phenomenon has spawned new ways of communication and engagement for consumers and companies alike. In particular, social networking sites such as Facebook have gained popularity and a strong membership base due to its pervasive nature and opportunities for seamless engagement. However, the concept of online consumer engagement on social media is an emerging construct in marketing literature and remains vague due to lack of academic research and empirical support. Furthermore, many organizations are unclear about the value and financial returns that investment in social media brings to their business. As such, the aim of this study is to provide an exploratory insight into the construct of customer engagement in the realm of online social media. In addition, the impact of customer engagement activity on driving purchase intent is also examined. The social networking site, Facebook was used as a basis to evaluate the research objectives, using a quantitative online survey. The findings suggest that online social media users engage with brands on Facebook on a superficial level, rather than on an in-depth basis. More importantly, consumer engagement on social media is found to have a significant impact on driving purchase intention for the brand. This study provides insights into the role that consumer engagement on social media brings to the business and presents practical implications for marketing practitioners. Finally, directions and opportunities for future research are also discussed.